Extended discussion of information for informed consent for participation in clinical trials - Hon, Yoon Khee (Cochrane Database Syst Rev, 2017)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: To assess the effects of 'extended discussion' compared with conventional methods of informed consent for participation in clinical trials for understanding, willingness to participate and anxiety.